HEARING READINESS (Tufts Archival Research Center, 2007)
Confidential; Marginalia; Outline of a presentation on indoor air quality (IAQ). Provides names of people who will be speaking regarding specific topics related to indoor air as well as the names of organizations which can provide evidence supporting the tobacco industry. Includes slides of case studies on clean indoor air (e.g. air quality on airplanes).